2012
DOI: 10.1159/000336002
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Geographical Variation of Myasthenia Gravis in the Province of Pavia, Italy

Abstract: Background and Aims: Previous studies have reported a prevalence estimate of myasthenia gravis (MG) from 7.7 to 11.1 per 100,000 inhabitants in Europe. Moreover, the study of the geographical distribution of MG should be useful to generate specific hypotheses. The aims are to estimate MG prevalence and to investigate its geographical variation in a delimited area in Northern Italy. Methods: The primary source of data was the MG database of the Neurological Institute of Pavia and all other sources of case colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 58 publications
3
14
0
1
Order By: Relevance
“…Number of patients 1 6 -1 9 2 0 -2 9 3 0 -3 9 4 0 -4 9 5 0 -5 9 6 0 -6 9 7 0 -7 9 > 8 0 1 6 -1 9 2 0 -2 9 3 0 -3 9 4 0 -4 9 5 0 -5 9 6 0 -6 9 7 0 -7 9 > 8 0 1 6 -1 9 2 0 -2 9 3 0 -3 9 4 0 -4 9 5 0 -5 9 6 0 -6 9 7 0 -7 9 > 8 0 1 6 -1 9 2 0 -2 9 3 0 -3 9 4 0 -4 9 5 0 -5 9 6 0 -6 9 7 0 -7 9 > 8 0 1 6 -1 9 2 0 -2 9 3 0 -3 9 4 0 -4 9 5 0 -5 9 6 0 -6 9 7 0 -7 9 > 8 0 1 6 -1 9 2 0 -2 9 3 0 -3 9 4 0 -4 9 5 0 -5 9 6 0 -6 9 7 0 -7 9 > 8 0 1 6 -1 9 2 0 -2 9 3 0 -3 9 4 0 -4 9 5 0 -5 9 6 0 -6 9 7 0 - We did not find any prevalence or clinical differences in thymoma MG between the Norway and the Netherlands. Thymoma occurrence rates were similar to other population-based studies in northern as well as in southern Europe, estimated to be around 10% [2,3,33] . The prevalence rate found is exactly the same as it was in the Netherlands in 2000 [5] .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Number of patients 1 6 -1 9 2 0 -2 9 3 0 -3 9 4 0 -4 9 5 0 -5 9 6 0 -6 9 7 0 -7 9 > 8 0 1 6 -1 9 2 0 -2 9 3 0 -3 9 4 0 -4 9 5 0 -5 9 6 0 -6 9 7 0 -7 9 > 8 0 1 6 -1 9 2 0 -2 9 3 0 -3 9 4 0 -4 9 5 0 -5 9 6 0 -6 9 7 0 -7 9 > 8 0 1 6 -1 9 2 0 -2 9 3 0 -3 9 4 0 -4 9 5 0 -5 9 6 0 -6 9 7 0 -7 9 > 8 0 1 6 -1 9 2 0 -2 9 3 0 -3 9 4 0 -4 9 5 0 -5 9 6 0 -6 9 7 0 -7 9 > 8 0 1 6 -1 9 2 0 -2 9 3 0 -3 9 4 0 -4 9 5 0 -5 9 6 0 -6 9 7 0 -7 9 > 8 0 1 6 -1 9 2 0 -2 9 3 0 -3 9 4 0 -4 9 5 0 -5 9 6 0 -6 9 7 0 - We did not find any prevalence or clinical differences in thymoma MG between the Norway and the Netherlands. Thymoma occurrence rates were similar to other population-based studies in northern as well as in southern Europe, estimated to be around 10% [2,3,33] . The prevalence rate found is exactly the same as it was in the Netherlands in 2000 [5] .…”
Section: Discussionsupporting
confidence: 88%
“…The studied area in the Netherlands is characterized by a high population density and urbanity, with large cities and an airport. Two recent studies examining the geographical variation have found more prevalent MG cases in the urban areas compared to the rural areas [2,45] . One could speculate whether the urban differences reflect individual behavior or exposure of exogenous environmental factors like, for example, air pollution influencing the disease development.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…La prevalencia descrita de MG oscila entre 5 y 24 casos por 100.000, representando los mayores de 65 años menos del 50% del total 7,8 . Estos estudios están realizados en grandes poblaciones o bien sobre diagnósticos del sistema de salud, circunstancias que pueden dificultar la correcta identificación de los casos para el cálculo de la prevalencia.…”
Section: Introductionunclassified